THE INFLUENCE OF SOCIAL MEDIA INSTAGRAM ON ROOM PURCHASE DECISION AT FAIRFIELD BY MARRIOTT BALI LEGIAN - Sari, Ni Made Asih Nirmala; Sadjuni, Ni Luh Gde Sri; Pratiwi, Kadek Andita Dwi (JURNAL BISNIS HOSPITALITI, 2023)
Fluctuations in occupancy rates is influenced by guests' purchasing decisions, one of factors can affect purchasing decisions is marketing, particularly via social media promotions. Instagram is  a key platform, trended for wide-reaching promotions, notably impacting room bookings. This study aims to analyze the impact of Instagram social media on room purchasing decisions at the Fairfield by Marriott Bali Legian.  The research employs a quantitative approach with a purposive sampling method with 100 surveyed guests who already stayed and followed the hotel on Instagram answered a 25-statement questionnaire. Data analysis is using SPSS for Windows Version 26. The research results indicate that Instagram social media (X) significantly influences room purchasing decisions (Y) at the Fairfield by Marriott Bali Legian, as evidenced by the significance value of 0.000 < 0.05 and a calculated tvalue > ttable of 10.027 > 1.984. The coefficient of determination analysis shows that Instagram social media has a moderate effect, accounting for 50.6% of the purchasing decisions, while the remaining 49.4% are influenced by other factors beyond the scope of this study. The overall value for the Instagram social media is 4.53, and for the purchasing decision, it's 4.54, both falling under the "very good" or "strongly agree" category.